Comparative Study Between Core Decompression in Low Grade AVN Of Femoral Head and Core Decompression with Intraosseous Ibandronate at a Teaching Hospital - Gadkari, Alok; Jha, Amrit (International Journal of Innovative Research in Medical Science, 2022)
Background: Many options for treatment of avascular necrosis have been described, including core decompression, vascularised and non-vascularised bone grafting, muscle pedicle bone grafting, bisphosphonates and various osteotomies. In present study we compared core decompression alone with core decompression & intraosseous ibandronate in low grade AVN of femoral head at a teaching hospital. Material and Methods: Present study was a prospective, interventional study conducted in patients with low grade AVN of Femoral head, Ficat Stage I or II, fit for surgery, willing to participate. Preoperatively patients were randomly divided into two groups as core decompression alone & core decompression with intraosseous ibandronate. Results: During study period total 30 patients underwent surgery; patients were randomly divided into two groups as core decompression (n=15) & core decompression with intraosseous ibandronate (n=15). General characteristics such as age, gender, side, co-morbidities, Ficat Staging & Pre-Operative Harris Hip Score were comparable in both groups & difference was not significant statistically. Post-Operative Harris Hip Score was more than 60 in 9 (60%) patients from core decompression with intraosseous ibandronate group as compared to 6 (40%) patients from core decompression group & difference was significant statistically. Minor complications were observed in both groups, managed conservatively. None of study patients required THA during study period. Conclusion: Better results were noted in core decompression with intraosseous ibandronate group as compared to core decompression group.